2012
DOI: 10.1098/rspb.2012.2082
|View full text |Cite
|
Sign up to set email alerts
|

Mouth asymmetry in the textbook example of scale-eating cichlid fish is not a discrete dimorphism after all

Abstract: Individuals of the scale-eating cichlid fish, Perissodus microlepis, from Lake Tanganyika tend to have remarkably asymmetric heads that are either left-bending or right-bending. The 'left' morph opens its mouth markedly towards the left and preferentially feeds on the scales from the right-hand side of its victim fish, and the 'right' morph bites scales from the victims' left-hand side. This striking dimorphism made these fish a textbook example of their astonishing degree of ecological specialization and as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 39 publications
(116 reference statements)
3
74
0
1
Order By: Relevance
“…; Kusche et al . ), rather than the two clear discrete states originally described (Hori ). These findings challenged also the single gene determination model (Hori ; Hori et al .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…; Kusche et al . ), rather than the two clear discrete states originally described (Hori ). These findings challenged also the single gene determination model (Hori ; Hori et al .…”
Section: Introductionmentioning
confidence: 87%
“…This appears to be the case of P. microlepis, whose equal abundance of both morphs observed within populations (Hori ; Kusche et al . ) is considered maintained by the advantage of the less frequent morph (known as negative frequency‐dependent selection; Hori ; Nakajima et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, scale-eater populations always remain much smaller than their prey populations. Lastly, lateral jaw asymmetry has evolved in scale-eating specialists at least four times independently across a wide range of foraging strategies and habitats (from Amazonia to Lake Tanganyika to the mesopelagic ocean: [31], [32], [34], [36]; but also see [40]). This suggests that laterally asymmetric jaws may be a universally adaptive trait for scale-eaters by allowing lateral attacks while pursuing prey, whereas symmetrical jaws may require perpendicular alignment with the prey.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies found either bimodal [184,185] or unimodal [186,187] distributions of measures of asymmetry in the mouth region. Also, there is evidence that the distribution of asymmetry in larvae is unimodal [188] and that both genetic factors [188,189] and plasticity [186] influence the asymmetry of the mouth in adults.…”
Section: Antisymmetrymentioning
confidence: 99%